Major contributing factors to the lower level of connection to the existing sewer network in Addis Ababa: the case of the Kality catchment - Ali, Mohammed; Robele, Sirak (Frontiers in Environmental Engineering, 2023)
In Addis Ababa, many households did not connect to a sewer network even when they passed in front of their homes. This study was designed to investigate major factors that have contributed to the lower level of connection to existing sewer network in Kality catchment of Addis Ababa city. A household survey was conducted using questionnaire to capture customers’ reasons that have hindered them from connecting to sewers. Accordingly, lack of awareness, connection fee, topography, customers’ preference to onsite sanitations over sewer, customers’ unwillingness to reinstate fence or pavement in their compound, and unreliability of service given by the water utility were found to be the main reasons. The survey results were analyzed with binary logistic regression model using SPSS software. Except topography (p value 0.792) and connection fee (p value 0.446), the rest four independent variables had significant p values of less than 0.05 that implied a good model. Customers’ preference to onsite sanitations over sewers followed by reliability of service given by water utility, and then customers’ unwillingness to reinstate fence or pavement in their compound was the most determining factors that have contributed to the lower level of user’s interest to sewer connection. However, lack of awareness and information also played crucial role in defining the rate of connection to sewers in Kality catchment of Addis Ababa city. The study also revealed that there was a gap in legislation and its enforcement; there were neither a regulator nor regulation for monitoring wastewater management including mandatory connection to sewer in the city.